Diazepam's antifungal activity in fluconazole-resistant Candida spp. and biofilm inhibition in C. albicans: evaluation of the relationship with the proteins ALS3 and SAP5. Issue 3 (9th March 2021) - Juvêncio da Silva, Lisandra; Dias Barroso, Fátima Daiana; Vieira, Lucas Sousa; Carlos Mota, Daniel Roberto; da Silva Firmino, Bruna Kelly; Rocha da Silva, Cecília; de Farias Cabral, Vitória Pessoa; Cândido, Thiago Mesquita; Sá, Lívia Gurgel do Amaral Valente; Barbosa da Silva, Wildson Max; Silva, Jacilene; Marinho, Emmanuel Silva; et al.
Abstract : The genus Candida spp. has been highlighted as one of the main etiological agents causing fungal infections, with Candida albicans being the most prominent, responsible for most cases of candidemia. Due to its capacity for invasion and tissue adhesion, it is associated with the formation of biofilms, mainly in the environment and hospital devices, decreasing the effectiveness of available treatments. The repositioning of drugs, which is characterized by the use of drugs already on the market for other purposes, together with molecular-docking methods can be used aiming at the faster development of new antifungals to combat micro-organisms. This study aimed to evaluate the antifungal effect of diazepam on mature C. albicans biofilms in vitro and its action on biofilm in formation, as well as its mechanism of action and interaction with structures related to the adhesion of C. albicans, ALS3 and SAP5. To determine the MIC, the broth microdilution test was used according to protocol M27-A3 (CLSI, 2008). In vitro biofilm formation tests were performed using 96-well plates, followed by molecular-docking protocols to analyse the binding agent interaction with ALS3 and SAP5 targets. The results indicate that diazepam has antimicrobial activity against planktonic cells of Candida spp. and C. albicans biofilms, interacting with important virulence factors related to biofilm formation (ALS3 and SAP5). In addition, treatment with diazepam triggered a series of events in C. albicans cells, such as loss of membrane integrity, mitochondrial depolarization and increased production of EROs, causing DNA damage and consequent cell apoptosis.